(untitled) (REMUNOM, 2026)
This study aimed to analyze the challenges of the import process of an Amazonian freight forwarding company. It employed the scientific-technological method in its scientific dimension to generate answers to the guiding questions and the central question, using a semi-structured interview guide administered to professionals in each department, which constitutes the company’s core activity. The data were analyzed using semantic and content analyses, organized into summary tables, and the results were interpreted comparatively against the theoretical framework developed from the state of the art on import processes. The results indicated that: a) nine challenges exist in the import process, b) faced by all units that comprise its core activities, c) these challenges represent small parts of the organizational macro-challenge of achieving the target negotiated with clients, d) the causes of the challenges are logistical, technological, communicational, and financial, and e) the complexity is high when negotiation is involved, medium in technical and technological aspects, and low when bureaucracy is present. The conclusion was that the challenges of the import process are primarily external and uncontrollable, necessitating organizational adaptation.